ЎРТА ОСИЁДА БРОНЗА ДАВРИДА МИГРАЦИЯЛАР ВА ЭТНОМАДАНИЙ ЖАРАЁНЛАР - Абдуллаев, У.И. (SCIENCE and SOCIETY, 2019)
The article analyzes the ethnocultural processes and socio-economic system of the Bronze Age in Central Asia. The migrations to Central Asia have been staged.
Keywords: bronze Age; Ethnocultural Process; Political Process; Socio-Economic System; Population Migration; Urbanization; History of State